2016
DOI: 10.1007/s13577-015-0129-z
|View full text |Cite
|
Sign up to set email alerts
|

Sperm midpiece apoptotic markers: impact on fertilizing potential in in vitro fertilization and intracytoplasmic sperm injection

Abstract: The aim of this study was to investigate the relationship between apoptotic markers present in human spermatozoa, namely phosphatidylserine translocation (PST) from the inner to the outer layer of the cytomembrane and the active form of caspase-3 (c3) versus the fertilizing potential of male gametes in conventional in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) models. A total of 116 male patients treated with their partners for infertility underwent basic semen analysis and an assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
11
0
5
Order By: Relevance
“…Apoptosis plays an essential role in the spermatogenesis and sperm maturation [56]; however, abnormal apoptosis resulting from the mitochondrial pathways, alterations in testes can also negatively affect spermatogenesis and sperm count [57]. Apoptosis markers can be used to assess the capability of fertilization in spermatozoa [58]. In this study concerning apoptosis, a greater significant increase in the activation of caspase 3/7 in spermatozoa was observed in the subchronic fluoride exposure under diabetic conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Apoptosis plays an essential role in the spermatogenesis and sperm maturation [56]; however, abnormal apoptosis resulting from the mitochondrial pathways, alterations in testes can also negatively affect spermatogenesis and sperm count [57]. Apoptosis markers can be used to assess the capability of fertilization in spermatozoa [58]. In this study concerning apoptosis, a greater significant increase in the activation of caspase 3/7 in spermatozoa was observed in the subchronic fluoride exposure under diabetic conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Increasing numbers of studies have demonstrated that apoptosis, as an ongoing physiological phenomenon, seems to exert a strong influence on the decrease in spermatozoa quality [5, 6]. In stored spermatozoa, apoptosis may directly affect the changes in typical spermatozoa quality parameters, including motility, acrosome status, membrane integrity, and phosphatidylserine distribution [1416]. Previous studies revealed that freezing and thawing-induced apoptosis is inversely correlated with spermatozoa motility and plasma membrane integrity during cryopreservation [15, 19, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have considered that spermatozoa exhibit little transcriptional activity and, thus, do not undergo apoptosis [911]. Nevertheless, recent considerable evidences have strongly demonstrated the occurrence of apoptosis in spermatozoa, exhibiting signs of phosphatidylserine exteriorization, caspase activation, and DNA damage [1114]. Clinical studies and laboratory findings have reported that apoptosis impacts the functional quality of spermatozoa [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Due that semen quality assessed by WHO criteria does not fully predict male fertility [ 8 ], new methodologies have been developed to determine sperm quality and function, including proteomic analysis [ 9 , 10 ], apoptotic markers [ 11 ], oxidative status [ 12 , 13 ], DNA adducts [ 14 ], and DNA methylation status [ 15 ], obtaining good associations with male fertility. Unfortunately, these techniques are expensive and difficult to include in the operational process in andrology laboratories, and therefore have not had continuity.…”
Section: Introductionmentioning
confidence: 99%